2017
DOI: 10.17294/2330-0698.1416
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Using Patient Experience Feedback to Improve Health Care Quality: Systematic Review and Framework Development

Abstract: "patient experience data" or "patient satisfaction data" or "patient feedback data" and "quality improvement" or "quality assurance" or "quality of care" 89,964 (patient or customer or user or client) [MeSH] and (experience or satisfaction or feedback) [MeSH] and (data or result* or information) [MeSH] and ("quality improvement" or "quality assurance" or "quality of care") 10,331 (patient or customer or user or client) [MeSH] and (experience or satisfaction or feedback) [MeSH] and (data or result* or info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 24 publications
1
36
0
4
Order By: Relevance
“…had 88% responses of satisfaction, but the same questions received significant drops in satisfaction reports when asked in a negative manner. "Perceived quality" is a subjective, cognitive assessment of what and how something happened, which is why many view patient experience evaluations as the most effective way to understand the patient perspective (Kumah et al, 2017). Patient perspective has received recognition on a policy level: patient experience, alongside clinical effectiveness and safety, is considered one of the "three pillars of quality" at the epicenter of NHS health programs.…”
Section: Drivers Of Patient Perspective Evaluations Filling In Gaps Imentioning
confidence: 99%
“…had 88% responses of satisfaction, but the same questions received significant drops in satisfaction reports when asked in a negative manner. "Perceived quality" is a subjective, cognitive assessment of what and how something happened, which is why many view patient experience evaluations as the most effective way to understand the patient perspective (Kumah et al, 2017). Patient perspective has received recognition on a policy level: patient experience, alongside clinical effectiveness and safety, is considered one of the "three pillars of quality" at the epicenter of NHS health programs.…”
Section: Drivers Of Patient Perspective Evaluations Filling In Gaps Imentioning
confidence: 99%
“…Ultimately, to move this work forward and ensure data gathered is useful in a quality improvement setting, it needs to be summarized and presented in a way that allows health care managers and health care professionals to identify actionable targets for quality improvement (10,11). Much of the published literature focuses on the development of questionnaires designed to assess the quality of care from the patient's perspective, but there is little research on how to effectively use patient data for quality improvement (8,(134)(135)(136)(137)(138)(139)(140)(141)(142). A recent systematic review highlights the lack of research in this area and proposes a framework for using patient data in quality improvement that involves "making sense of data" (benchmarking and comparing results), "communicating and explaining data" (interpret and disseminate results) and "planning for improvement" (discuss results with stakeholders to identify and select priorities for improvement).…”
Section: Figure 2-3 Framework For Health Services Research (Adapted Fmentioning
confidence: 99%
“…A recent systematic review highlights the lack of research in this area and proposes a framework for using patient data in quality improvement that involves "making sense of data" (benchmarking and comparing results), "communicating and explaining data" (interpret and disseminate results) and "planning for improvement" (discuss results with stakeholders to identify and select priorities for improvement). However, they point out that in order to effectively use patient experience data it is essential that an organization's leaders can understand the data collected (140). Barriers to using patient-reported data have been identified and tend to fall into three categories: characteristics of the organization, characteristics of the data, or characteristics of the individuals using the data (8,10,136).…”
Section: Figure 2-3 Framework For Health Services Research (Adapted Fmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Specifically, the authors systematically reviewed how clinical organizations synthesize and react to patient feedback and concluded that, because this data is often analyzed out of context, creating effective action plans based on patient feedback can be difficult. Therefore, they propose a framework for making sense of and communicating findings from patient surveys, then developing plans for quality improvement.…”
mentioning
confidence: 99%